FACTORS AFFECTING LOW ACADEMIC ACHIEVEMENT OF UNDERGRADUATE MEDICAL STUDENTS: STUDENT EXPERIENCE - Rika Lisiswanti; Merry Indah sari; Drisnaf Swastyardi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Low achievement is one of the problems in higher education. Many factors that can cause student failure or low student achievement such as motivation, time management, learning strategy, socioeconomic, family, environment, presence, and student’s interest. The purpose of this study was to investigate the factors affecting low academic achievement of undegraduate medical students in the Medical Faculty of Lampung University.Methods: The study method was qualitative study with phenomenological approach and data was collected with a semi-structured interview. This study was conducted in Faculty of Medicine Universitas Lampung, in 2017. The study population was students in the first year, second year, and third year. Sample taken with purposive sampling obtained 17 students. Inclusion criteria: students who achieved Grade Point Average (GPA) < 2 and who participated in this study. Data was analysed by using thematic analysis.Results: The number of respondents was 7 male students and 10 female students. The low achievement was caused by a lack of learning strategy, lack of motivation, psychological problems, family problems, and health problems.Conclusion: The factors affecting low achievement were lack of learning strategy, lack of motivation, psychological problems, family problems, and health.